Nature-Derived Cellulose-Based Composite Separator for Sodium-Ion Batteries - Jo, Jae Hyeon; Jo, Chang-Heum; Qiu, Zhengfu; Yashiro, Hitoshi; Shi, Liyi; Wang, Zhuyi; Yuan, Shuai; Myung, Seung-Taek (Frontiers in Chemistry, 2020)
Sodium-ion batteries (SIBs) are emerging power sources for the replacement of lithium-ion batteries. Recent studies have focused on the development of electrodes and electrolytes, with thick glass fiber separators (~ 380 μm) generally adopted. In this work, we introduce a new thin (~ 50 μm) cellulose–polyacrylonitrile–alumina composite as a separator for SIBs. The separator exhibits excellent thermal stability with no shrinkage up to 300 °C and electrolyte uptake with a contact angle of 0°. The sodium ion transference number, tNa+, of the separator is measured to be 0.78, which is higher than that of bare cellulose (tNa+: 0.31). These outstanding physical properties of the separator enable the long-term operation of NaCrO2 cathode/ hard carbon anode full cells in a conventional carbonate electrolyte, with capacity retention of 82% for 500 cycles. Time-of-flight secondary-ion mass spectroscopy analysis reveals the additional role of the Al2O3 coating, which is transformed into AlF3 upon long-term cycling owing to HF scavenging. Our findings will open the door to the use of cellulose-based functional separators for high-performance SIBs.